ABOUT THE DEFINITION OF OPPORTUNITIES AND CONDITIONS FOR IMPROVEMENT OF THE FINANCIAL RESOURCES MANAGEMENT OF THE STATE UKRAINE - Petrenko, V. P.; Danyluk-Chernykh, I. M. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The purpose of this article is to seek and identify the conditions for the harmonization of the interests of financial market participants, in particular, the regulator – the National Bank of Ukraine, the banking system and consumers of financial services. The article contains interpretation of the financial system as a classical self-regulated link covered by some feedback. The authors of concluded that the innovative potential of financial management should be sought in improving financial management components of the integral intelligence of human resources system. The basics of forming Pareto-optimal interaction of financial market participants are considered. The synarch-syntellect-synergetic model of the behavior of the management and human resources is presented can become the most effective solution because of the appeal to the system’s "shared mind" in order to obtain the desired result.